Non-B subtypes account for a large proportion of clustered primary HIV-1 infections in Italy. (20th April 2022) - Bozzi, Giorgio; Fabeni, Lavinia; Abbate, Isabella; Berno, Giulia; Muscatello, Antonio; Taramasso, Lucia; Fabbiani, Massimiliano; Nozza, Silvia; Tambussi, Giuseppe; Rusconi, Stefano; Giacomelli, Andrea; Focà, Emanuele; et al.
Abstract : Objectives and design: Using pol sequences obtained for routine resistance testing, we characterised the molecular patterns of HIV-1 transmission and factors associated with being part of a transmission cluster among individuals who in 2008–2014 presented with primary HIV-1 infection (PHI) at 11 urban centres across Italy. Methods: Pol sequences were obtained by Sanger sequencing. Transmission clusters were identified by phylogenetic analysis (maximum likelihood method, confirmed by Bayesian analysis). Multivariable logistic regression explored factors associated with a participant being part of a transmission cluster. Results: The PHI cohort comprised 186 participants (159/186, 85.5% males) with median age 44 years, median CD4 count 464 cells/mm 3 and median plasma HIV-1 RNA 5.6 log10 copies/mL. Drug resistance associated mutations were found in 16/186 (8.6%). A diversity of non-B subtypes accounted for 60/186 (32.3%) of all infections. A total of 17 transmission clusters were identified, including 44/186 (23.7%) participants. Each cluster comprised 2–6 sequences. Non-B subtypes accounted for seven clusters and 22/44 (50%) of clustered sequences. In multivariable logistic regression analysis, factors associated with being part of a transmission cluster comprised harbouring a non-B subtype (adjusted OR (adjOR) 2.28; 95% CI 1.03 to 5.05; p=0.04) and showing a lower plasma HIV-1 RNA (adjOR 0.80, 95% CI 0.64 to 0.99; p=0.04). Conclusions: There was a large contribution of diverse non-B subtypes to transmission clusters among people presenting with acute or recent HIV-1 infection in this cohort, illustrating the evolving dynamics of the HIV-1 epidemic in Italy, where subtype B previously dominated.